The Status of Knowledge, Attitude, and Practice in Relation to Major Mosquito Borne Diseases Among Community of Niger State, Nigeria (African Journal of Biomedical Research, 2022)
A survey at the household level was carried out on KAP regarding major mosquito-borne diseases. Data was collected from 967 respondents based on the population. The results revealed that 78.80% of the respondents had formal education at least basic (primary) education. Of the 967 respondents, 71.04% and 68.98% of the population had the right knowledge of major mosquito diseases and mosquito vectors, respectively. Common sources of information on these diseases are mainly from health workers (29.78%) and broadcasting media 26.88%. Transmission of the diseases is linked to mosquito bites by 66.80%, usually at night (76.11% ), while 20.41% and 23.84% of the respondents knew other means and times. 100% of the respondents correctly knew the signs and symptoms of any one of the diseases. General lack of clearing of house surrounding (43.85%), draining of gutter (24.30%), bush clearing (20.06%), proper disposal of empty cans (11.79%) keeps more mosquitoes. Mosquito-treated bed nets (53.05%) are the most preventive method against mosquito bite practice, mosquito coils (20.57%), window screen netting (11.79%), cloth covering (7.80%), and traditional plant repellents (6.83%) attest to be effective. On attitudes toward treatment, 52.64% seek treatment at the nearest hospital/clinic within 1 – 3 days of the symptoms; however, some of the respondents visit drug stores/chemists (23.88%) for treatment. Given the success of the public enlightenment campaign launched by the government on mosquito diseases control, more is needed to be done against self-medication and visiting of medical stores for treatment, to avert the danger of these practices in the areas.